2015
DOI: 10.1177/0145482x1510900504
|View full text |Cite
|
Sign up to set email alerts
|

Using Constant Time Delay to Teach Braille and the Nemeth Code for Mathematics and Science Notation to Students Making the Transition from Print to Braille

Abstract: Introduction Many students with adventitious vision loss or progressive vision loss need to transition from print to braille as a primary literacy medium. It is important that this transition is handled efficiently so that the student can have continued access to a literacy medium and make progress in the core curriculum. For this study, we used constant time delay to teach literary braille contractions and Nemeth Code for Mathematics and Science Notation (hereafter, Nemeth Code) braille symbols to learners wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…A functional relation was replicated with all three participants. The results of this study corroborate findings of previous research (Hooper et al, 2014;Ivy & Hooper, 2015), suggesting that constant time delay is a promising practice to teach braille word recognition. In addition, the results suggest that verbal controlling prompts are sufficient and effective to teach highly motivating words to young, beginning braille readers with multiple disabilities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A functional relation was replicated with all three participants. The results of this study corroborate findings of previous research (Hooper et al, 2014;Ivy & Hooper, 2015), suggesting that constant time delay is a promising practice to teach braille word recognition. In addition, the results suggest that verbal controlling prompts are sufficient and effective to teach highly motivating words to young, beginning braille readers with multiple disabilities.…”
Section: Discussionsupporting
confidence: 91%
“…Data were collected using event recording on a trial-by-trial basis. Five possible responses were mutually exclusive and exhaustive, and identical to those previously used for braille literacy (Hooper et al, 2014;Ivy & Hooper, 2015). These responses were "correct anticipation" (an independent, correct response); "correct wait" (a prompted, correct response); "nonwait error" (an error prior to prompt); "wait error" (an error after prompt); and "no response."…”
Section: Response Definitions and Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they had success with three of the four participants, there was a great deal of variability in the data. Based on the success of constant time delay to teach functional vocabulary words, Ivy and Hooper (2015) conducted another study using constant time delay to teach academic vocabulary. In that study, they used 3 ϫ 5 index cards to teach academic vocabulary words to two students (a third participant learned notation in the Nemeth Braille Code for Mathematics and Science Notation).…”
mentioning
confidence: 99%
“…Indeed, five studies have demonstrated the effectiveness of using CTD to teach braille words and contractions, including teaching novel English Braille American Edition (EBAE) words, Nemeth Code symbols, and/or dot-five contractions to braille readers (Hooper et al, 2014; Ivy et al, 2017; Ivy & Hooper, 2015; Moss, 2016; Wilcox, 2014). These prior studies all involved researchers as the ones who delivered the instruction to students with VI.…”
mentioning
confidence: 99%